Method for extracting lithium from lithium ore and lithium salt

By adding specific additives to the transformation and roasting process of lithium ore, and performing acidification and roasting and leaching treatment, the problem of knotting is easily encountered during the transformation and roasting of lithium feldspar is solved, which improves the lithium recovery rate and roasting efficiency and reduces the pressure of solid waste treatment.

CN119800101APending Publication Date: 2025-04-11BYD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411333645.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Lithium-permeable feldspar is prone to kneading during the high-temperature roasting transformation stage, resulting in low lithium recovery rate, waste of energy consumption, reduced rotary kiln life, and may even cause production lines to be shut down.

Method used

By mixing lithium ore with additives such as activated carbon, concentrated sulfuric acid and high-melting metal oxides for transformation and calcining, then acidizing and calcining with concentrated sulfuric acid, and finally leaching with water to obtain a lithium-containing leaching solution, effectively preventing the occurrence of halo rings.

Benefits of technology

This method significantly improves lithium recovery, reduces the amount of slag after leaching, reduces the treatment pressure of solid waste, and improves the safety and efficiency of the roasting process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800101A_ABST
    Figure CN119800101A_ABST
Patent Text Reader

Abstract

The invention discloses a method for extracting lithium from lithium ore and a lithium salt. The method for extracting the lithium from the lithium ore comprises the following steps: mixing the lithium ore with an additive, and carrying out transformation roasting to obtain the lithium ore with a transformed crystal structure; the additive comprises at least one of activated carbon, concentrated sulfuric acid and metal oxide; the melting point of the metal oxide is higher than the transformation roasting temperature; mixing the lithium ore with the transformed crystal structure with concentrated sulfuric acid, and then acidizing and roasting to obtain acidized clinker; and mixing the acidified clinker with water, and leaching to obtain a lithium-containing leachate. According to the method for extracting the lithium from the lithium ore, the ring forming phenomenon in the transformation roasting process can be effectively prevented, and the lithium recovery rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium battery technology, and in particular to a method for extracting lithium from lithium ore and lithium salts. Background Art

[0002] At present, the most mined and applied lithium minerals in the world are spodumene, lepidolite, petalite and so on, and most of the raw materials for lithium industry come from lithium ore resources. Lithium minerals such as spodumene and petalite play an important role in the production of lithium-ion batteries. Taking petalite as an example, petalite is a relatively cheap emerging lithium ore, and its structure does not contain fluorine elements, which is relatively safe during smelting. In recent years, petalite has received widespread attention. However, petalite is prone to ring formation during the high-temperature roasting transition stage, which will lead to low lithium recovery rate, waste of energy consumption, and reduced life of rotary kiln. In severe cases, it may even cause the shutdown of the production line. Therefore, it is of great significance to explore how to prevent the ring formation phenomenon during the transition roasting of petalite. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a method for extracting lithium from lithium ore and a lithium salt. The method for extracting lithium from lithium ore of the present application can effectively prevent the ringing phenomenon during the transition roasting process and improve the lithium recovery rate.

[0004] The first aspect of the present application provides a method for extracting lithium from lithium ore. According to an embodiment of the present application, the method for extracting lithium from lithium ore includes:

[0005] The lithium ore is mixed with an additive and then subjected to transformation roasting to obtain a lithium ore with a transformed crystal structure; the additive comprises at least one of activated carbon, concentrated sulfuric acid and a metal oxide; the melting point of the metal oxide is higher than the transformation roasting temperature;

[0006] The lithium ore containing the transformed crystal structure is mixed with concentrated sulfuric acid and then acidified and roasted to obtain acidified clinker;

[0007] The acidified clinker is mixed with water and then leached to obtain a lithium-containing leaching solution.

[0008] The present application adds additives during the transformation roasting process of lithium ore, which is beneficial to preventing mineral ringing, improving lithium recovery rate, reducing the amount of slag after leaching, and reducing the pressure of solid waste treatment.

[0009] In a second aspect, the present application proposes a lithium salt obtained by the above-mentioned method of extracting lithium from lithium ore.

[0010] The method for extracting lithium from lithium ore provided in the present application has a high lithium recovery rate, less slag mass after leaching, and less pressure on solid waste treatment.

[0011] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0013] Figure 1 The XRD pattern of petalite in the examples of the present application is shown.

[0014] Figure 2 The TG-DSC curve of petalite in the example of the present application under argon atmosphere is shown.

[0015] Figure 3 The SEM image of the ring after transformation of petalite in the example of the present application is shown.

[0016] Figure 4 The XRD pattern of spodumene in the examples of the present application is shown.

[0017] Figure 5 The TG-DSC curve of spodumene in the examples of the present application under argon atmosphere is shown. DETAILED DESCRIPTION

[0018] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0019] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0020] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0021] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0022] The first aspect of the embodiment of the present application provides a method for extracting lithium from lithium ore, comprising:

[0023] The lithium ore is mixed with an additive and then subjected to transformation roasting to obtain a lithium ore with a transformed crystal structure; the additive comprises at least one of activated carbon, concentrated sulfuric acid and a metal oxide; the melting point of the metal oxide is higher than the transformation roasting temperature;

[0024] The lithium ore containing the transformed crystal structure is mixed with concentrated sulfuric acid and then acidified and roasted to obtain acidified clinker;

[0025] The acidified clinker is mixed with water and then leached to obtain a lithium-containing leaching solution.

[0026] The above-mentioned "transformation roasting" means that spodumene and petalite are transformed into β-spodumene through high-temperature roasting. The above-mentioned "ring formation" means that during the roasting process, the impurities in the minerals are partially melted under the action of high temperature, and then solidified during the cooling process and adhered to the inner wall of the kiln body to form one or more layers of hardened ring-shaped substances.

[0027] The embodiment of the present application adds additives during the transition roasting process of lithium ore, which helps prevent mineral ringing, improves lithium recovery rate, reduces the amount of slag after leaching, and reduces the pressure of solid waste treatment.

[0028] Since lithium ore contains some low melting point impurities, such as tourmaline, pyrite and jarosite, etc., melting will occur during the transition roasting process, and after melting, the mixture will stick together, which is prone to ring formation. In the embodiment of the present application, a high melting point additive (the melting point of the additive is higher than the transition roasting temperature) is added, and after being evenly mixed with the lithium ore, a certain dilution effect is played, and the proportion of low melting point impurities in the lithium ore is reduced, thereby achieving an anti-ringing effect.

[0029] In addition, activated carbon powder as an additive has a certain reducing effect on the one hand, which can reduce some metal oxides (such as hematite and wurtzite) to metal elements, increase the melting point and avoid ring formation. On the other hand, the activated carbon powder that is not completely burned during the roasting process is evenly embedded between the ore particles, which can wrap the molten minerals and avoid overall sintering.

[0030] In addition, concentrated sulfuric acid as an additive will expand in volume after being mixed with lithium ore, increasing the gaps between particles in the lithium ore. As a result, some low-melting-point impurities in the lithium ore will still have certain gaps after melting, reducing the probability of adhesion of the molten material and preventing the occurrence of ring formation.

[0031] In the embodiment of the present application, concentrated sulfuric acid is added during the second stage of roasting for acidification roasting. Since the boiling point of concentrated sulfuric acid is about 337°C, acidification roasting at a temperature below this temperature can prevent the volatilization of concentrated sulfuric acid and ensure the full reaction of lithium ore and concentrated sulfuric acid after the crystal structure transformation. During the acidification roasting process, the amount of concentrated sulfuric acid added is relatively small, the material flux during roasting is small, the slag mass after leaching is small, and the pressure of solid waste treatment is small.

[0032] According to an embodiment of the present application, the lithium ore includes at least one of petalite and spodumene.

[0033] In the embodiment of the present application, at least one of petalite and spodumene can be selected and mixed with additives for use in transition roasting, which can effectively prevent ring formation, improve lithium recovery rate, reduce the amount of concentrated sulfuric acid used in acid roasting, and reduce the amount of slag after leaching.

[0034] According to an embodiment of the present application, the additive satisfies at least one of the following:

[0035] The activated carbon includes at least one of fruit shell activated carbon and wood-based charcoal;

[0036] The concentrated sulfuric acid is concentrated sulfuric acid with a mass percentage concentration of 98%;

[0037] The metal oxides include magnesium oxide.

[0038] In the embodiment of the present application, the activated carbon can be prepared by using wood and fruit shell as raw materials through activation. The wood includes at least one of poplar, pine and straw; and the fruit shell includes at least one of coconut shell and apricot shell.

[0039] In the embodiments of the present application, the additive satisfies at least one of the above conditions, which can help improve the anti-ringing effect during the transformation roasting process of lithium ore and improve the lithium recovery rate.

[0040] According to an embodiment of the present application, the mass ratio of lithium ore to additive is 1:(0.02-0.2). In a specific example, the mass ratio of lithium ore to additive is 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.2, etc.

[0041] In the present application, the dosage of lithium ore and additives meets the above conditions, which improves the effect of preventing ringing during the transition roasting process of lithium ore while reducing costs.

[0042] According to an embodiment of the present application, the additive satisfies at least one of the following:

[0043] The additive is activated carbon, and the mass ratio of lithium ore to the additive is 1:0.04-0.15; in specific examples, the mass ratio of lithium ore to the additive is 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, etc.

[0044] The additive is concentrated sulfuric acid, and the mass ratio of lithium ore to the additive is 1:0.04-0.15; in specific examples, the mass ratio of lithium ore to the additive is 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, etc.

[0045] The additive is a metal oxide, and the mass ratio of lithium ore to the additive is 1:0.1 to 0.15. In a specific example, the mass ratio of lithium ore to the additive is 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, etc.

[0046] In the present application, the dosage of lithium ore and additives meets the above conditions, which is beneficial to further improve the effect of preventing ringing during the transition roasting process of lithium ore.

[0047] According to an embodiment of the present application, in the transition roasting, the control parameters include: the roasting temperature is 1000℃~1200℃; and / or the roasting time is 10min~90min. In a specific example, the transition roasting temperature is 1000℃, 1010℃, 1020℃, 1030℃, 1040℃, 1050℃, 1060℃, 1070℃, 1080℃, 1090℃, 1100℃, 1110℃, 1120℃, 1130℃, 1140℃, 1150℃, 1160℃, 1170℃, 1180℃, 1190℃, 1200℃, etc.

[0048] In the embodiment of the present application, under the above-mentioned roasting temperature and roasting time conditions, the lithium ore undergoes a crystal structure transformation, such as all or part of petalite is transformed into β-spodumene, such as all or part of α-spodumene is transformed into β-spodumene. At the same time, at the roasting temperature, additives such as activated carbon and metal oxides will not melt, and the water-proof ringing effect is fully exerted.

[0049] According to the embodiments of the present application, the mass ratio of lithium ore containing the transformed crystalline structure to concentrated sulfuric acid is 1:(0.15-0.25). In specific examples, the mass ratio of lithium ore containing the transformed crystalline structure to concentrated sulfuric acid is 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.20, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, etc.

[0050] In the embodiments of the present application, when acidification roasting is performed, the amount of concentrated sulfuric acid added meets the above conditions. The less concentrated sulfuric acid is added, the smaller the material flux is during roasting, the less slag mass is after leaching, and the lower the pressure of solid waste treatment.

[0051] Furthermore, the concentrated sulfuric acid is concentrated sulfuric acid with a mass percentage concentration of 98%.

[0052] According to an embodiment of the present application, during the acidification roasting process, the control parameters include: the roasting temperature is 250°C to 320°C, and / or the roasting time is 20min to 120min. In a specific example, the acidification roasting temperature is 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, etc. In a specific example, the acidification roasting time is 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, etc.

[0053] In the second stage of roasting, concentrated sulfuric acid is added for acid roasting. Since the boiling point of concentrated sulfuric acid is about 337°C, acid roasting at a temperature below this temperature can prevent the volatilization of concentrated sulfuric acid and ensure the full reaction of lithium ore and concentrated sulfuric acid after the crystal structure transformation. The acid roasting temperature of this application is relatively low, which is conducive to reducing energy consumption.

[0054] According to an embodiment of the present application, during the acidification roasting process, the control parameters include: the roasting temperature is 275°C to 300°C, and / or the roasting time is 40min to 60min. In a specific example, the acidification roasting temperature is 275°C, 277°C, 280°C, 282°C, 285°C, 287°C, 290°C, 292°C, 295°C, 297°C, 300°C, etc. In a specific example, the acidification roasting time is 40min, 45min, 50min, 55min, 60min, etc.

[0055] The embodiment of the present application further selects the above-mentioned acidification roasting conditions to ensure sufficient reaction between the lithium ore and concentrated sulfuric acid after the crystal structure transformation, effectively prevent the volatilization of concentrated sulfuric acid, and reduce energy consumption.

[0056] According to an embodiment of the present application, a method for extracting lithium from lithium ore comprises:

[0057] S1000: Obtain lithium ore powder.

[0058] S2000: Transformation roasting. The lithium ore is mixed with additives and then subjected to transformation roasting to obtain lithium ore with a transformed crystal structure; the additives include at least one of activated carbon, concentrated sulfuric acid and metal oxides; the melting point of the metal oxide is higher than the transformation roasting temperature;

[0059] S3000: Acidification and roasting. The lithium ore containing the transformed crystal structure is mixed with concentrated sulfuric acid and then acidified and roasted to obtain acidified clinker;

[0060] S4000: Slurry leaching. The acidified clinker is mixed with water and then leached to obtain a lithium-containing leaching solution.

[0061] Furthermore, in the step of obtaining lithium ore powder, the bulk lithium ore can be crushed and then repeatedly finely ground until it can pass through a 60-100 mesh sieve.

[0062] Furthermore, after the transition roasting, the cooled lithium ore after the transition roasting is finely ground to pass through a 150-200 mesh sieve, and the sieved material is stirred and mixed with concentrated sulfuric acid for acidification roasting.

[0063] Furthermore, the slurry leaching step includes: grinding the acidified clinker to 150 μm to 75 μm; then, mixing the clinker with pure water in a mass ratio of 1:1 to 1:5, and stirring and leaching at room temperature; finally, obtaining a lithium-containing leachate after filtering.

[0064] The second aspect of the embodiment of the present application provides a lithium salt obtained by the preparation method of the above-mentioned method for extracting lithium from lithium ore. Further, the lithium salt includes lithium sulfate.

[0065] The method for extracting lithium from lithium ore provided in the embodiment of the present application has a high lithium recovery rate, less slag mass after leaching, and less pressure on solid waste treatment.

[0066] It should be noted that the features and advantages described above for the method for extracting lithium from lithium ore in the first aspect of the present application are also applicable to the lithium salt in the second aspect of the present application and will not be repeated here.

[0067] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0068] Example 1

[0069] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0070] Step 2: Mix the sieved petalite and additive (coconut shell activated carbon powder) in a mass ratio of 1:0.02 and then calcine at 1090°C for 50 minutes.

[0071] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add it into a mixer with concentrated sulfuric acid at a mass ratio of 1:0.19, and stir evenly to obtain a standby material.

[0072] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 300°C for 50 minutes.

[0073] Step 5: After the roasted product is crushed and finely ground, it is stirred for 50 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are filtered to obtain.

[0074] In the method provided in this embodiment, after transition roasting, the minerals did not form rings, but very few ore adhesion particles with a diameter of about 1 cm appeared.

[0075] The lithium extraction rate is 97.8%, the lithium content in the leached slag is 0.04%, and the slag mass is reduced by about 1.5% compared with the raw material mass.

[0076] Example 2

[0077] Step 1: Crush and grind the petalite to pass through a 60-mesh sieve.

[0078] Step 2: The sieved petalite and additive (coconut shell activated carbon powder) were mixed evenly in a mass ratio of 1:0.08 and then calcined at 1040°C for 60 minutes.

[0079] Step 3: After cooling, the transformed petalite is finely ground to pass through a 150-mesh sieve, and is added into a mixer with concentrated sulfuric acid (mass percentage concentration of 98%) at a mass ratio of 1:0.18 and stirred evenly to obtain a standby material.

[0080] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 320°C for 60 minutes.

[0081] Step 5: After the roasted product is crushed and finely ground, it is stirred for 60 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0082] The method provided in this embodiment makes the minerals loose and free of rings after transition roasting.

[0083] The lithium extraction rate is 97.1%, the lithium content in the leached slag is 0.04%, and the slag mass is reduced by about 1.4% compared with the raw material mass.

[0084] Example 3

[0085] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0086] Step 2: Mix the sieved petalite and additive (coconut shell activated carbon powder) in a mass ratio of 1:0.10 and then calcine at 1100°C for 60 minutes.

[0087] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add it into a mixer with concentrated sulfuric acid at a mass ratio of 1:0.19, and stir evenly to obtain a standby material.

[0088] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 300°C for 60 minutes.

[0089] Step 5: After the roasted product is crushed and finely ground, it is stirred for 60 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0090] The method provided in this embodiment significantly improves the mineral ring formation after transition roasting.

[0091] The lithium extraction rate is 98.7%, the lithium content in the leached slag is 0.02%, and the slag mass is reduced by about 1.5% compared with the raw material mass.

[0092] Example 4

[0093] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0094] Step 2: Mix the sieved petalite and additive (coconut shell activated carbon powder) in a mass ratio of 1:0.10 and then calcine at 1150°C for 40 minutes.

[0095] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add it into a mixer with concentrated sulfuric acid at a mass ratio of 1:0.2 and stir evenly to obtain a standby material.

[0096] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 275°C for 40 minutes.

[0097] Step 5: After the roasted product is crushed and finely ground, it is stirred for 30 minutes at a liquid-to-solid ratio of 1.5, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0098] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0099] The lithium extraction rate is 99.3%, the lithium content in the leached slag is 0.01%, and the slag mass is reduced by about 1.5% compared with the raw material mass.

[0100] Example 5

[0101] Step 1: Crush and grind the petalite to pass through a 60-mesh sieve.

[0102] Step 2: Mix the sieved petalite and additive (coconut shell activated carbon powder) in a mass ratio of 1:0.2 and then calcine at 1150°C for 50 minutes.

[0103] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add concentrated sulfuric acid in a mass ratio of 1:0.18 into a mixer, and stir evenly to obtain a standby material.

[0104] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 300°C for 50 minutes.

[0105] Step 5: After the roasted product is crushed and finely ground, it is stirred for 40 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0106] The method provided in this embodiment does not form rings in the minerals after transition roasting, and the looseness is similar to that before roasting, indicating that there is no need to further increase the proportion of coconut shell activated carbon powder.

[0107] The lithium extraction rate is 98.9%, the lithium content in the leached slag is 0.02%, and the slag mass is reduced by about 1.5% compared with the raw material mass.

[0108] Example 6

[0109] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0110] Step 2: Mix the sieved petalite and additive (coconut shell activated carbon powder) in a mass ratio of 1:0.17 and then calcine at 1150°C for 40 minutes.

[0111] Step 3: After cooling, grind the transformed petalite to pass through a 150-mesh sieve, add concentrated sulfuric acid in a mass ratio of 1:0.15 into a mixer, and stir evenly to obtain a standby material.

[0112] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 280°C for 40 minutes.

[0113] Step 5: After the roasted product is crushed and finely ground, it is stirred for 30 minutes at a liquid-to-solid ratio of 1.5, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0114] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0115] The lithium extraction rate is 98.5%, the lithium content in the leached slag is 0.02%, and the slag mass is reduced by about 1.5% compared with the raw material mass.

[0116] Example 7

[0117] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0118] Step 2: The sieved petalite and the additive (magnesium oxide) were mixed evenly in a mass ratio of 1:0.10 and then calcined at 1075°C for 60 minutes.

[0119] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add concentrated sulfuric acid in a mass ratio of 1:0.20 into a mixer, and stir evenly to obtain a standby material.

[0120] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 300°C for 60 minutes.

[0121] Step 5: After the roasted product is crushed and finely ground, it is stirred for 60 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0122] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0123] The lithium extraction rate is 97.8%, the lithium content in the leached slag is 0.03%, and the slag mass is reduced by about 1.3% compared with the raw material mass.

[0124] Example 8

[0125] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0126] Step 2: The sieved petalite and the additive (magnesium oxide) were mixed evenly in a mass ratio of 1:0.15 and then calcined at 1150° C. for 40 min.

[0127] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add concentrated sulfuric acid in a mass ratio of 1:0.25 into a mixer, and stir evenly to obtain a standby material.

[0128] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 275°C for 40 minutes.

[0129] Step 5: After the roasted product is crushed and finely ground, it is stirred for 40 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0130] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0131] The lithium extraction rate is 98.9%, the lithium content in the leached slag is 0.01%, and the slag mass is reduced by about 1.3% compared with the raw material mass.

[0132] Example 9

[0133] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0134] Step 2: The sieved petalite and the additive (concentrated sulfuric acid, mass percentage concentration of 98%) were mixed evenly at a mass ratio of 1:0.03, and then the mixture was transformed and roasted at 1100° C. for 60 min.

[0135] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add concentrated sulfuric acid (mass percentage concentration of 98%) into a mixer at a mass ratio of 1:0.17, and stir evenly to obtain a standby material.

[0136] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 300°C for 60 minutes.

[0137] Step 5: After the roasted product is crushed and finely ground, it is stirred for 60 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0138] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0139] The lithium extraction rate is 98.1%, the lithium content in the leached slag is 0.02%, and the slag mass is reduced by about 2% compared with the raw material mass.

[0140] Example 10

[0141] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0142] Step 2: The sieved petalite and additive A (concentrated sulfuric acid) were mixed evenly in a mass ratio of 1:0.04 and then calcined at 1150°C for 40 minutes.

[0143] Step 3: After cooling, grind the transformed petalite to pass through a 200-mesh sieve, add it into a mixer with concentrated sulfuric acid at a mass ratio of 1:0.2 and stir evenly to obtain a standby material.

[0144] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 275°C for 40 minutes.

[0145] Step 5: After the roasted product is crushed and finely ground, it is stirred for 30 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0146] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0147] The lithium extraction rate is 99.3%, the lithium content in the leached slag is 0.01%, and the slag mass is reduced by about 2% compared with the raw material mass.

[0148] Embodiment 11

[0149] Step 1: Crush and grind the spodumene until it can pass through a 100-mesh sieve.

[0150] Step 2: Mix the sieved spodumene and additive (coconut shell activated carbon powder) in a mass ratio of 1:0.05 and then calcine at 1050°C for 40 minutes.

[0151] Step 3: After cooling, grind the transformed spodumene to pass through a 200-mesh sieve, add concentrated sulfuric acid in a mass ratio of 1:0.17 into a mixer, and stir evenly to obtain a standby material.

[0152] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 275°C for 40 minutes.

[0153] Step 5: After the roasted product is crushed and finely ground, it is stirred for 30 minutes at a liquid-to-solid ratio of 2, a temperature of 25° C., and a stirring speed of 350 rpm. After the leaching is completed, the lithium-containing leaching solution and leaching residue are obtained by filtration.

[0154] The method provided in this embodiment does not form rings in the minerals after transition roasting.

[0155] The lithium extraction rate is 98.8%, the lithium content in the leached slag is 0.01%, and the slag mass is reduced by about 2% compared with the raw material mass.

[0156] Comparative Example 1

[0157] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0158] Step 2: Mix the sieved petalite and sulfate (sodium sulfate) in a mass ratio of 1:1.0 and press into bricks. The mineral bricks are calcined at 1150℃ for 60 minutes.

[0159] Step 3: After cooling, the transformed bricks are crushed and finely ground to pass through a 200-mesh sieve. The finely ground ore powder is stirred for 60 minutes at a liquid-to-solid ratio of 2, a temperature of 25°C, and a stirring speed of 350 rpm. After leaching, the lithium-containing leaching solution and leaching residue are filtered to obtain.

[0160] The method provided in this comparative example causes the bricks to melt slightly during transition firing.

[0161] The lithium extraction rate is about 85.1%, the lithium content in the leached slag is about 0.31%, and the slag mass is increased by about 20% compared with the raw material mass. Compared with the sulfuric acid method of the present application, the sulfate method has a large amount of slag and a low lithium extraction rate.

[0162] Comparative Example 2

[0163] Step 1: Crush and grind the petalite until it can pass through a 100-mesh sieve.

[0164] Step 2: The sieved petalite is transformed and roasted at 1150℃ for 60min. During the transformation, the petalite adheres to the inner wall of the kiln.

[0165] Step 3: After cooling, the transformed petalite is taken out and finely ground to pass through a 200-mesh sieve, and is added into a mixer with concentrated sulfuric acid (mass percentage concentration of 98%) at a mass ratio of 1:0.25 and stirred evenly to obtain a standby material.

[0166] Step 4: Add the spare material into the rotary kiln and carry out acidification roasting at 300°C for 60 minutes. After crushing and grinding the roasted product, stir it for 60 minutes at a liquid-solid ratio of 2, a temperature of 25°C, and a stirring speed of 350rpm. After the leaching is completed, filter to obtain the lithium-containing leachate and leach residue.

[0167] The method provided in this embodiment results in mineral ring formation after transition roasting.

[0168] The lithium extraction rate is about 92.4%, the lithium content in the leached slag is less than 0.12%, and the slag mass is reduced by about 2% compared with the raw material mass. Compared with the addition of additives during transformation, the lithium extraction rate is significantly reduced.

[0169] Petalite

[0170] In the present application, the element contents and phase compositions of the petalite used in the above-mentioned embodiments and comparative examples are shown in Tables 1 and Figure 1As shown. The lithium grade in petalite is 1.46%, and the aluminum content is relatively high. The physical composition of the petalite is mainly quartz, petalite, albite and calcium feldspar.

[0171] The TG-DSC (thermogravimetric analysis (TG)-differential scanning calorimetry (DSC)) curve of petalite in argon atmosphere is as follows: Figure 2 As shown, the ore has an endothermic peak at around 970°C, indicating that some minerals in the ore begin to melt.

[0172] The surface morphology of the ring-forming petalite after calcination without additives is as follows: Figure 3 As shown, some mineral particles melt and thus sinter as a whole.

[0173] Table 1 Element content of petalite

[0174]

[0175] Spodumene

[0176] In the present application, the element content and phase composition of the spodumene used in the above examples are shown in Tables 2 and Figure 4 As shown in the figure, the lithium grade in spodumene is 1.64%, and the aluminum content is relatively high. The physical composition of the spodumene is mainly quartz, spodumene and albite.

[0177] The TG-DSC (thermogravimetric analysis (TG) - differential scanning calorimetry (DSC)) curve of spodumene in argon atmosphere is as follows: Figure 5 As shown, the ore exhibits endothermic peaks at around 300°C and 1100°C, indicating that some minerals in the ore begin to melt.

[0178] Table 2 Element content of spodumene

[0179]

[0180] Lithium content test:

[0181] 1. Lithium content detection method.

[0182] Dry the lithium slag after stirring and washing twice, weigh 0.1g of the dried slag, put it in a polytetrafluoroethylene beaker, add 5ml of concentrated sulfuric acid and 5ml of hydrofluoric acid, mix well and heat it on a flat heater at 200℃ for 2h. After 2h, add 10ml of hydrochloric acid and 5ml of nitric acid to the polytetrafluoroethylene beaker and continue heating for 40min. After heating, cool it down, make the volume to 100ml, and measure its lithium content by ICP (Inductively Coupled Plasma). The lithium in the leachate is measured by ICP after diluting the leachate 1000 times.

[0183] The lithium extraction rate is calculated by formula (1):

[0184]

[0185] In formula (1), A represents the lithium recovery rate, %; C represents the lithium concentration in the leachate, mg / L; V represents the volume of the leachate, L; β represents the lithium content in the leached residue, %; and m represents the mass of the leached residue, g.

[0186] 2. Lithium content test results.

[0187] Table 3 Comparison of smelting effects between the embodiment and the comparative example

[0188] sample Whether sintering Lithium extraction rate / % Lithium content in slag / % Example 1 no 97.8 0.04 Example 2 no 97.5 0.04 Example 3 no 98.7 0.02 Example 4 no 99.3 0.01 Example 5 no 98.9 0.02 Example 6 no 98.5 0.02 Example 7 no 97.8 0.03 Example 8 no 98.9 0.01 Example 9 no 98.1 0.02 Example 10 no 99.3 0.01 Embodiment 11 no 98.8 0.01 Comparative Example 1 yes 85.1 0.31 Comparative Example 2 yes 92.4 0.12

[0189] The test results are shown in Table 3. The lithium recovery rate in each embodiment of the present application is significantly higher than that in the comparative example, indicating that the addition of additives during roasting can not only effectively prevent petalite from forming a kiln during roasting transformation, but also contribute to the complete transformation of petalite and improve the lithium extraction rate.

[0190] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for extracting lithium from lithium ore, characterized in that: include: The lithium ore is mixed with an additive and then subjected to transformation roasting to obtain a lithium ore with a transformed crystal structure; the additive comprises at least one of activated carbon, concentrated sulfuric acid and a metal oxide; the melting point of the metal oxide is higher than the transformation roasting temperature; The lithium ore containing the transformed crystalline structure is mixed with concentrated sulfuric acid and then acidified and roasted to obtain acidified clinker; The acidified clinker is mixed with water and then leached to obtain a lithium-containing leaching solution.

2. The method for extracting lithium from lithium ore according to claim 1, characterized in that: The lithium ore includes at least one of petalite and spodumene.

3. The method for extracting lithium from lithium ore according to claim 1 or 2, characterized in that: The additive satisfies at least one of the following: The activated carbon includes at least one of fruit shell activated carbon and wood activated carbon; The concentrated sulfuric acid is concentrated sulfuric acid with a mass percentage concentration of 98%; The metal oxide includes magnesium oxide.

4. The method for extracting lithium from lithium ore according to any one of claims 1 to 3, characterized in that: The mass ratio of the lithium ore to the additive is 1:(0.02-0.2).

5. The method for extracting lithium from lithium ore according to any one of claims 1 to 4, characterized in that: At least one of the following is met: The additive is activated carbon, and the mass ratio of the lithium ore to the additive is 1:0.04-0.15; The additive is concentrated sulfuric acid, and the mass ratio of the lithium ore to the additive is 1:0.04-0.15; The additive is a metal oxide, and the mass ratio of the lithium ore to the additive is 1:0.1-0.

15.

6. The method for extracting lithium from lithium ore according to any one of claims 1 to 5, characterized in that: In the transition roasting, the control parameters include: The calcination temperature is 1000° C. to 1200° C.; and / or the calcination time is 10 min to 90 min.

7. The method for extracting lithium from lithium ore according to any one of claims 1 to 6, characterized in that: The mass ratio of the lithium ore after the crystalline structure transformation to concentrated sulfuric acid is 1: (0.15-0.25).

8. The method for extracting lithium from lithium ore according to any one of claims 1 to 7, characterized in that: In the acidification roasting process, the control parameters include: the roasting temperature is 250° C. to 320° C., and / or the roasting time is 20 min to 120 min.

9. The method for extracting lithium from lithium ore according to any one of claims 1 to 8, characterized in that: During the acidification roasting process, the control parameters include: the roasting temperature is 275° C. to 300° C., and / or the roasting time is 40 min to 60 min.

10. A lithium salt obtained by the method for extracting lithium from lithium ore according to any one of claims 1 to 9.

Citation Information

Cited By

  • Method for extracting lithium from lithium ore through low-temperature roasting

    CN120796738A